Design and research on optimization of single point mooring system. (August 2019) - Wang, Ying; Xie, Haiyan; Zheng, Enxi
Abstract: In this paper, we establish a statics model to analyze the force balance of the buoys, four steel pipes and steel buckets, and we derive the relationship between the inclination angle of steel pipes and steel buckets and the draught depth and wind speed, which is solved by moment in mechanics. Next, by applying the catenary curve's equation to per unit of anchor chain, we can obtain the vertical height of anchor chain, thus the total depth of sea water can be obtained. Finally, the variable step search algorithm is used to search the draught depth, and we can obtain each parameter of the optimization result.